The effectiveness of sound metaphor in television advertising - Maysoon Kadhim Jasim; Baida Noori Thaib (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The audio metaphor in television commercials occupies a wide space at the level of employment and expression of the subject of the advertisement, and today, in light of the technical developments of metaphor, has become an aesthetic value in the structure and formulation of the contents and ideas presented in the work that emerge from the value of the advertisement. It enhances the aesthetic and expressive value of advertising and as a result of many developments in the expressiveness of sound metaphor in television commercials.